Quetiapine is not associated with increase in prolactin secretion in contrast to haloperidol - Atmaca, M; Kuloglu, M; Tezcan, E; Canatan, H; Gecici, O (Elsevier Science Inc, 2002)
Background. Typical antipsychotic drugs frequently cause hyperprolactinemia and even galactorrhea. In addition, these side effects may result in noncompliance with antipsychotic treatment. Capacity to avoid hyperprolactinemia has been accepted as one atypical criterion. The aim of the present study was to compare effects of haloperidol, the most commonly used antipsychotic, and quetiapine, a novel antipsychotic agent used in Turkey, on serum prolactin (PRL) levels. Methods. The study consisted of 35 females diagnosed with schizophrenia according to the Diagnostic and Statistical Manual of Mental Disorders, 4(th) ed. (DSM-IV). Thirty-five patients in a drug-free period for at least 2 weeks were included to randomized quetiapine (n = 18) and haloperidol (n = 17) treatment group. All patients were assessed by Brief psychiatric rating scale (BPRS), Positive and negative syndrome scale (PANSS), and Extrapyramidal symptoms rating scale (ESRS). PRL levels were measured both at the beginning and at the sixth week of the study. Results. Both treatment groups exhibited significant improvements in clinical signs as evaluated by BPRS and PANSS. While there was no significant difference in PRL level between groups at the beginning of the study, control prolactin (PRL) levels were significantly lower in quetiapine compared to haloperidol group. While no quetiapine group patients exhibited galactorrhea, we observed that two patients from the haloperidol group had galactorrhea related to hyperprolactinemia. Conclusions. The present study revealed that quetiapine is not associated with increase in PRL secretion in contrast to the conventional antipsychotic haloperidol. (C) 2002 IMSS. Published by Elsevier Science Inc.
Keywords: quetiapine; haloperidol; prolactin; hyperprolactinemia